2021
DOI: 10.1111/tbed.14008
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the use of animal health platforms: User’s needs, preferences and constraints

Abstract: Animal health information systems or risk analysis tools are indispensable not only for animal health surveillance, but also to observe the evolution and risk of disease incursion into a disease-free area. Given the various information that can be derived from these both animal information systems and risk analysis tools, different international and national organizations have customized or created their own systems/tools

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Our analysis identified limited knowledge of existing databases and a lack of human resources for extracting and processing data. We confirmed the importance of centralizing data access and descriptive epidemiology in the process of EI [ 33 ].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Our analysis identified limited knowledge of existing databases and a lack of human resources for extracting and processing data. We confirmed the importance of centralizing data access and descriptive epidemiology in the process of EI [ 33 ].…”
Section: Discussionsupporting
confidence: 74%
“…Strategies that would allow quicker assessment of risks of introduction include the centralized provision of predefined sets of determinants and health information by disease and location, as well as alerts when new validated datasets are available. These needs expressed by practitioners highlight concrete expectations in line with the general recommendations of connecting data from a wide range of sources [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Strategies that would allow quicker assessment of risks of introduction include the centralized provision of prede ned sets of determinants and health information by disease and location, as well as alerts when new validated datasets are available. These needs expressed by practitioners highlight concrete expectations in line with the general recommendations of connecting data from a wide range of sources (23,24).…”
Section: Data Collection and Processingmentioning
confidence: 82%
“…A shared challenge for these generic risk assessment tools is to keep them up and running and to have added value to policy makers in setting priorities for preventive measures and surveillance. Bianchini et al ( 81 ) did a survey on the use of animal health information systems and risk analysis tools among professionals in animal and public health around the world. They concluded that the main areas of interest from these systems and tools are information on where diseases are present, pathways of introduction, and spread assessment.…”
Section: Discussionmentioning
confidence: 99%